Factors associated with Medicaid participation among infants born with birth defects in Texas, 2010–2014. Issue 15 (11th August 2022) - Swanson, Justin; Shumate, Charlie; Agopian, A. J.; Mitchell, Laura E.; Canfield, Mark A.; Salemi, Jason L.
Abstract: Background: Birth defects are major contributors to healthcare resource use, disability, and mortality, particularly during the perinatal period. As the nation's public insurance program for low‐income individuals, Medicaid funds a large proportion of healthcare costs associated with birth defects. Here, we explore birth defect‐related factors associated with Medicaid participation in the first year of life. Methods: Infants born with birth defects between 2010 and 2014 were linked from the Texas Birth Defects Registry to the state's Medicaid claims database. Variation in Medicaid participation was examined by individual birth defect and by birth defect characteristics. The associations between covariates and Medicaid participation are described using percentages and adjusted prevalence ratios (APR). Results: Of the 107, 968 infants included in this study, 55, 172 (51.1%) participated in Medicaid. Medicaid participation ranged from 12.1% for anencephaly to 77.8% for total anomalous pulmonary venous connection. An indicator of defect severity was associated with an increased likelihood of participation (APR = 1.22, 95% CI: 1.20–1.23). Medicaid participation was 60.8% for individuals with multiple major defects, compared with 45.4% for those without (APR = 1.24, 95% CI: 1.22–1.25). Among individual birth defects, Medicaid participation was almost universally higher for those co‐occurring with other major defects. Conclusions: We detected large variations in Medicaid participation by individual birth defect. Infants participating in Medicaid tended to have more severe defects and were more likely to have multiple major defects. Medicaid claims databases can serve as valuable sources of data for surveillance efforts and observational studies, but care should be taken when generalizing findings.